2008
DOI: 10.1002/cm.20272
|View full text |Cite
|
Sign up to set email alerts
|

Myosin‐Va mediates RNA distribution in primary fibroblasts from multiple organs

Abstract: Myosin-Va has been shown to have multiple functions in a variety of cell types, including a role in RNA transport in neurons. Using primary cultures of cells from organs of young dilute-lethal (Myo5a d-l /Myo5a d-l ) null mutant mice and wild-type controls, we show that in some, but not all, tissues, RNA distribution is dramatically different in the homozygous null mutant cells. The dependence of RNA localization on myosin-Va correlates with the relative abundance of the brainspecific splicing pattern of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 44 publications
3
18
0
Order By: Relevance
“…Multiple functions have been assigned to this actin-dependent molecular motor, including the transport of melanosomes, smooth endoplasmic reticulum, recycling endosomes, neurotransmitter vesicles, mRNA (Reck-Peterson et al 2000, Langford 2002, Salerno et al 2008, and neuroendocrine vesicles (Rudolf et al 2003). A role for MYO5A in tumor cell migration, invasion, and metastasis has recently been described (Du et al 2007, Lan et al 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple functions have been assigned to this actin-dependent molecular motor, including the transport of melanosomes, smooth endoplasmic reticulum, recycling endosomes, neurotransmitter vesicles, mRNA (Reck-Peterson et al 2000, Langford 2002, Salerno et al 2008, and neuroendocrine vesicles (Rudolf et al 2003). A role for MYO5A in tumor cell migration, invasion, and metastasis has recently been described (Du et al 2007, Lan et al 2010.…”
Section: Discussionmentioning
confidence: 99%
“…It could be proposed therefore that directed ZBP1 transport is carried out by and requires a fine-tuned regulation of multiple microtubule and actin motors. Myosin Va (MyoVa) is a fast processive myosin that transports diverse cargoes such as vesicles (Kogel et al, 2010; Wu et al, 1997), neurofilaments (Rao et al, 2002), mitochondria (Pathak et al, 2010) and ER (Wagner et al, 2011), as well as RNA (Krauss et al, 2009; Salerno et al, 2008; Yoshimura et al, 2006). Mutations of MyoVa cause Griscelli syndrome in humans and dilute-lethal phenotype in mice, which display defects in skin/coat color and have neurological phenotypes (Pastural et al, 1997; Takagishi and Murata, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Myosin Va has been found associated with several RNA binding proteins in a messenger ribonucleoprotein (mRNP) complex precipitated from a mouse brain extract (8). The intracellular distribution of RNA is dramatically altered in primary cells derived from dilute-lethal (myosin Va-null) mice (9). Yoshimura et al (10) have shown that myosin Va mediates the translocation of TLS (translated in liposarcoma) and its target RNA, Nd1-L, into dendritic spines, and myosin V is involved in targeting oskar mRNA to the posterior pole of the Drosophila oocyte (11).…”
mentioning
confidence: 99%